الفائض التأميني وتطبيقاته في شركة الراجحي للتكافل Insurance surplus and its applications in al-Rajhi takaful company - Laeba, Muhammad; Negasi, Mohamed Ibrahim; Duramea, Ismail; Mohamed Zaki, Hesham Mahmoud (IIUM, 2020)
The study aims to clarify the rulings of insurance surplus that have caused several problems to arise around it, both at the theoretical and practical levels. Scholars have differed on whether it is permissible or not. To achieve the desired goal, the researchers shed light on what insurance surplus is, and the rulings related to it, such as the ruling on the entitlement of subscribers and their company to insurance surplus. Additionally, this study explains the ruling on the company’s dealings with this surplus and how to distribute and invest it. Hence the researchers have also studied the company's applications for insurance surplus. This study follows the inductive approach for the texts and opinions that deal with this subject, and the analytical approach for their analysis and discussion. Moreover, this research intends to study the model of Al-Rajhi Takaful Company’s applications in insurance surplus and its related rulings.